ADAPTASI MODEL PEMBELAJARAN MAKE A MATCH DENGAN TALKING STICK UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS VIII SMP NEGERI 15 DUMAI - Nursian Nursian (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2019)
This study aims to improve their learning achievement after using the adaptation of the learning model to make a match and talking stick in a Social Sciences subject at SMP Negeri 15 Dumai. This research is collaborative classroom action research with stages of planning, action, observation, and reflection. This research was conducted at SMP Negeri 15 Dumai with research subjects of class VIII students with a total of 26 students. The results showed that the adaptation of the learning model make a match and talking stick was able to increase the average student learning, indicated by the fact that in the first cycle the implementation of learning reached 78.08 and in Cycle II it was achieved. 87.31 increase student learning activeness, indicated by the fact that in Cycle I 60.23%, and in cycle II 94.32% and improve student learning achievement, indicated by the fact that in the pre-cycle the percentage of students who attained mastery level was 34, 62% (9 students) and students who did not reach the mastery level were 65.38% (17 students); in the first cycle the percentage of students who reached the mastery level was 73.08% (19 students) and students who did not reach the mastery level were 26.92% (7 students); in Cycle II the percentage of students who reached the mastery level was 88.46% (23 students) and students who did not reach the mastery level were 11.54% (3 students). Based on the results of the study, it can be concluded that the adaptation of the learning model make a match and talking stick is able to improve the learning achievement of social subjects in class VIII students at SMP Negeri 15 Dumai.